Relating the Spherical representation of vocational interests to the HEXACO personality model - Holtrop, Djurre; Born, M.; de Vries, R. (Academic Press, 2015)
The present study extends previous research on interests-personality relations by comparing recent models of vocational interests (using the Personal Globe Inventory; PGI, Tracey, 2002) and personality (using the HEXACO-PI-R; Ashton, Lee, & de Vries, 2014) with each other. First, the structure of the Spherical representation was adequately replicated in a Dutch sample (N = 656). Second, in so far as comparisons were possible, the relations between interests and personality were found to be congruent with previous findings. Third, Prestige interests, the defining feature of the Spherical representation, were related, albeit weakly, to Openness to Experience and to Extraversion. Last of all, Honesty-Humility and Openness to Experience were related to profile elevation in interest scores. All results were obtained for normative and ipsatized scales, revealing several meaningful differences in interests-personality relations depending on the type of interest scoring procedure.